The Effect of Green Marketing Mix 7P on Coffee Product Purchase Decisions at MSMEs Coffee Shop Makassar - Fitriany; Dwinanda, Giri; Nugraha, I Made Widhi; Makkulau, Mochammad Mallingkaan; Mubyl, Mutiarini (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study examines the influence of Green Marketing Mix 7P on Coffee Product Purchase Decisions in MSME Coffee Shops in Makassar. Through SEM analysis with SmartPLS 4.0 analysis tool and involving 270 respondents, this study found that Green Place (environmentally friendly interior design) and Green Process (sustainable production process) have a significant influence on purchasing decisions. Meanwhile, Green Product, Green Price, Green Promotion, Green People, and Green Physical Evidence did not have a significant influence. This research provides important implications for MSME Coffee Shop actors in Makassar to focus on environmentally friendly interior design and implement sustainable production processes